High‐Resolution Patterning and Transferring of Graphene‐Based Nanomaterials onto Tape toward Roll‐to‐Roll Production of Tape‐Based Wearable Sensors. Issue 12 (17th November 2017) - Oren, Seval; Ceylan, Halil; Schnable, Patrick S.; Dong, Liang
Abstract: This paper reports on a simple and versatile method for patterning and transferring graphene‐based nanomaterials onto various types of tape to realize flexible microscale sensors. The method involves drop‐casting a graphene film on a prepatterned polydimethylsiloxane (PDMS) surface containing negative features by graphene suspensions, applying Scotch tape to remove the excess graphene from the nonpatterned areas of the PDMS surface, and then transferring the patterned graphene from the inside of the negative features at the PDMS surface onto a target tape. The feature size of transferred graphene patterns on the final tape is as small as a few micrometers. This method is easy to implement, but does not require the use of expensive equipment, except for needing a PDMS substrate containing negative features. This method has a high versatility in producing micropatterns of graphene‐based nanomaterials on different types of adhesive tape. For the purpose of application demonstration, flexible mechanical sensors and sensor arrays, smart gloves, and plant leaf sensors on tapes to realize real‐time monitoring of important signals indicating human motion and plant water transport behavior have been developed. This technology will open a new route for low‐cost, scalable, and roll‐to‐roll production of graphene‐based sensors on tape. Abstract : A facile method for patterning and transferring of graphene‐based sensing nanomaterials onto adhesive tape is developed toward low‐cost, installation‐free, wearable sensors. The minimum feature size of the transferred nanomaterials is on the order of a few micrometers. Wearable on‐tape plant leaf sensors, mechanical sensors, and smart gloves are demonstrated for real‐time monitoring of plant water transpiration and human motion.